2014
DOI: 10.1016/j.jpubeco.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Learning for a bonus: How financial incentives interact with preferences

Abstract: This paper investigates the effect of financial incentives on student performance and analyzes for the first time how the incentive effect in education is moderated by students' risk and time preferences. To examine this interaction we use a natural experiment that we combine with data from surveys and economic experiments on risk and time preferences. We not only find that students who are offered financial incentives for better grades have on average better first-and second-year grade point averages, but mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Third, regarding the problem of selection into occupations in principal, previous empirical studies have shown that teenagers who choose an apprenticeship at the age of fifteen have a strong preference for those occupations that are regionally available (Oswald & Backes-Gellner, 2014), which substantially restricts their spectrum for self-selection.…”
Section: Robustness Checksmentioning
confidence: 99%
“…Third, regarding the problem of selection into occupations in principal, previous empirical studies have shown that teenagers who choose an apprenticeship at the age of fifteen have a strong preference for those occupations that are regionally available (Oswald & Backes-Gellner, 2014), which substantially restricts their spectrum for self-selection.…”
Section: Robustness Checksmentioning
confidence: 99%
“…For a detailed description of the data seeOswald and Backes-Gellner (2014), who use early waves of the data to investigate the education production of grades.2 Grit, however, while characterizing the passion for long-term goals, is not merely a measure of time preferences: the correlation between the Grit measure and experimentally elicited time preferences in our data is only .1.…”
mentioning
confidence: 91%
“…Hence, we assumed that the availability of financial incentive attracted participants to join the program and explore the content, but was not powerful enough to drive them to spend more effort beyond Phase 2 of transformative learning even though participants would not receive the technology grant until they completed the program (Figure ). This seemed to be well supported by the result of Oswald and Backes‐Gellner's () study on the effectiveness of financial incentive at the beginning of a program. In addition, this assumption explained why the incentive availability did not predict participants' program completion.…”
Section: Discussionmentioning
confidence: 76%
“…Overall, the power of financial incentive did not sustain participants throughout the program. According to the findings of Oswald and Backes‐Gellner's () study, it only worked at the beginning of a long‐term program. Results of Brook et al's (2008) study in adult literacy learning demonstrated that financial incentives, when given in a small amount, had a negative effect on attendance.…”
Section: Factors Influencing Online Adult Trainingmentioning
confidence: 99%